Análise da estrutura e dinâmica da assembleia de peixes do trecho de cabeceira do Ribeirão Cambé, Londrina - PR - Alves, Nathália Trevisan (2015)
The structure and dynamics of fish assemblages tend to change as these changes occurs into the water system, the surrounding water body or even in the drainage basin. Thus, this study analyzed the structure and dynamics of fish assemblages in the water stream of Cambé (Londrina-PR), inserted in an urban basin. The fish and water collection occurred in 3 sites in the headwater stream in 2013 and 2014, one collection in each season. The collection of fish was done initially by manual fishing, with sampling effort of 40 minutes and three people, followed by electrofishing with the same effort. With the sampled water, the abiotic parameters were measured, such as pH, electrical conductivity, water temperature, dissolved oxygen and turbidity, using portable equipment. We collected 2,340 specimens of fish distributed in 6 orders, 8 families and 15 species. The most abundant species were P. reticulata and T. rendalli, both exotic species, and the species with greater biomass was G. brasiliensis. 80% of the collected species were considered constant in the stream, and only two accidental species and one as accessory. The spatial variation detected significate differences between sampled sites as the abundance of individuals and biomass, which is related to physiographic differences and anthropogenic interference. Site 3 showed the highest values in relation to parameters of diversity, while site 1 had the highest dominance. In the temporal analysis it wasn't detected differences between the seasons in relation to abundance and biomass, with the stream not showing a clear pattern of change throughout the year and between years. Site 2 is highlighted in the assessment of size distribution pattern, revealing the lowest average size due to collection of large numbers of immature individuals of T. rendalli, and individuals of larger size, which indicated the ambient capacity to favor larger species. Although locals 1 and 3 were classified as moderately degraded from ABC curves, the studied stretch was considered degraded, by influence of the results obtained in site 2 (high abundance of T. rendalli). The CCA confirmed previous standards and revealed that the water temperature and dissolved oxygen were most correlated with axis 1 and contributed to the segregation of site 2. Multivariate analysis also confirmed that site 3 showed greater diversity of species and participation of larger specimens, site 1 showed greater dominance values and electrical conductivity, which may indicate input to compounds originating from effluents and loading of urban materials.